Metagenomic and Metabolomic Profiling Reveals the Impact of High‐Fat Diet on Malignant Pleural Effusion - Qing‐Yu Chen; Ming‐Ming Shao; Shu‐Feng Dong; Huan‐Zhong Shi; Feng‐Shuang Yi (Thoracic Cancer)
ABSTRACT Background Malignant pleural effusion (MPE) is a common complication in the advanced stage of cancer. High‐Fat Diet (HFD)‐induced obesity has become a common metabolic background in cancer patients. Recent studies have demonstrated that HFD induces gut dysbiosis, resulting in alterations in metabolites and immune responses. However, its role in MPE remains unclear. Methods We established an MPE mouse model under both normal chow and HFD conditions. Metagenomic sequencing of fecal samples and untargeted metabolomics of plasma were performed to assess alterations in gut microbiota and systemic metabolites, respectively. Bioinformatic and statistical analyses were conducted to identify significant microbial taxa and metabolic pathways. Results HFD‐fed mice exhibited increased pleural effusion. Metagenome data of the intestinal microbiome and metabolome profiles of plasma metabolites revealed key taxa—Akkermansiaceae, Parabacteroides, and Muribaculaceae—as well as significant metabolic pathways involved in sphingolipid metabolism, glycerophospholipid metabolism, and steroid hormone biosynthesis. Conclusion These findings suggest that HFD may accelerate the MPE progression through modulation of gut microbiota and plasma metabolites, providing new strategies for prevention and treatment.